COVID-19 : How will European banks fare? - Aiyar, Shekhar (Washington, D.C International Monetary Fund (IMF), 2021)
This paper evaluates the impact of the crisis on European banks’ capital under a range of macroeconomic scenarios, using granular data on the size and riskiness of sectoral exposures. The analysis incorporates the important role of pandemic-related policy support, including not only regulatory relief for banks, but also policies to support businesses and households, which act to shield the financial sector from the real economic shock. (IMF page)
Acknowledgments -- Glossary -- Executive Summary -- 1. Introduction -- 2. Pre-Pandemic Bank Health -- 3. Banks’ Vulnerability to the Pandemic -- 4. Policy Measures to Support Banks, Firms, and Households -- 5. Analytical Framework -- 6. Results -- 7. Expanding the Analysis Beyond Euro Area Banks -- 8. Summary and Policy Implications
​Includes bibliographical references (P. 97-101).
Keywords: International banking; BANKS; RISK MANAGEMENT; COVID-19; ECONOMIC ASPECTS; EUROPE